1989
DOI: 10.1007/bf00276947
|View full text |Cite
|
Sign up to set email alerts
|

Predator-prey populations with parasitic infection

Abstract: A predator-prey model, where both species are subjected to parasitism, is developed and analyzed. For the case where there is coexistence of the predator with the uninfected prey, an epidemic threshold theorem is proved. It is shown that in the case where the uninfected predator cannot survive only on uninfected prey, the parasitization could lead to persistence of the predator provided a certain threshold of transmission is surpassed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
229
1
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 394 publications
(235 citation statements)
references
References 24 publications
4
229
1
1
Order By: Relevance
“…Anderson and May [3] showed that invasion of a resident predator-prey or host-parasite system by a new strain of parasites could cause destabilization and exhibit limit cycles. Hadeler and Freedman [17] observed a similar phenomenon. Mukherjee [25] analysed a prey-predator model with parasite infection and obtained conditions for persistence and impermanence.…”
Section: Introductionmentioning
confidence: 60%
“…Anderson and May [3] showed that invasion of a resident predator-prey or host-parasite system by a new strain of parasites could cause destabilization and exhibit limit cycles. Hadeler and Freedman [17] observed a similar phenomenon. Mukherjee [25] analysed a prey-predator model with parasite infection and obtained conditions for persistence and impermanence.…”
Section: Introductionmentioning
confidence: 60%
“…Anderson and May (1986) were considered the disease factor in a predator-prey dynamics and found that the pathogen tends to destabilize the predator-prey interaction. In Rosenzweig prey-predator model, an epidemic threshold (above which an infected equilibrium or an infected periodic solution appear) was determined by Hadeler and Freedman (1989). Chattopadhyay and Arino (1999) considered a three species eco-epidemiological model and determined extinction criteria of species and found condition for Hopf-bifurcation in an equivalent two-dimensional model.…”
Section: Introductionmentioning
confidence: 99%
“…Modelling of trophic interactions in the presence of infection is a major subject of ecoepidemiology, which is itself a rapidly growing branch of theoretical ecology. Since the first publications in this area [3,13,34], hundreds of various ecoepidemiological models have been suggested so far emphasizing various aspects of the field (for a brief review, see [35]). However, in most of the previous works, the authors assume that the predator is a specialist, i.e.…”
Section: Introductionmentioning
confidence: 99%